Validity of the Trait Emotional Intelligence Questionnaire (TEIQue) in a Brazilian Sample - Zuanazzi, Ana Carolina; Meyer, Gregory J.; Petrides, Konstantinos V.; Miguel, Fabiano Koich (Frontiers in Psychology, 2022)
The study of the relationship between reasoning and emotional processes is not new in Psychology. There are currently two main approaches to understanding the aspects related to these processes called emotional intelligence: the ability model and the trait model. This study focuses on the latter, analyzing the factor structure, reliability, and validity of the Trait Emotional Intelligence Questionnaire (TEIQue) in a Brazilian sample. 4314 adults with ages ranging from 18 to 60 years (M = 30.37; SD = 9.73) answered the TEIQue and other online instruments measuring emotional regulation, impulsiveness, alexithymia, loneliness, quality of life, positive and negative affect, personality traits, emotional perception, emotional understanding, and reasoning tests. The original four-factor structure of the TEIQue was replicated, Cronbach’s alphas ranged from .60 to .89 for the facets, and from .76 to .90 for the factors and global score. The correlations followed theoretically expected directions, showing a stronger pattern for self-report measures than for performance tasks. Our results corroborated previous studies with the TEIQue, confirming the psychometric adequacy of the instrument in the Brazilian context. Future studies may focus on participants with lower levels of education and additional external criteria, such as career preferences, job performance, and health.